Agricultural insurance schemes for the development of rural economy - Rahman Ibrahim Abdul (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In the last decades, agricultural production became more and more expensive. Nevertheless, there are a lot of risks that affect agricultural production and agricultural producers' income. This income instability determines many of them abandon their business. The paper will approach the agricultural risk management from the perspective of agricultural insurances, with a general presentation at EU level, and a special focus on the situation of Romania and Turkey. There will be analyzed the factors which contribute to the development agricultural insurances, as well as the effect of the later on the development of the agriculture sector in each country. The aim of the paper is to improve the understanding of the importance of the agricultural insurance schemes as a risk management tool and of its role in increasing the agricultural production in Romania, given that the rural area in this country is subject to many climatic risks which affect its stability. An important input of the paper will be the good practice of Turkey in this field. General conclusions and considerations will close the whole paper. The author will use different information sources from European and national level, such as reports, country fact sheets, etc…
Keywords: 330; agriculture insurance; rural area; risk management